1999
DOI: 10.1086/307731
|View full text |Cite
|
Sign up to set email alerts
|

Central Rotation Curves of Spiral Galaxies

Abstract: We present high-resolution central-to-outer rotation curves for Sb, SBb, Sc, and SBc galaxies. We discuss their general characteristics, particularly their central behavior, as well as dependencies on morphological types, activity, and peculiarity. The rotation curves generally show a steep nuclear rise and high-velocity central rotation, followed by a broad maximum in the disk and then a Ñat rotation due to the massive halo. Since the central high velocity and steep rise are common to all massive galaxies, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
251
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(271 citation statements)
references
References 24 publications
(47 reference statements)
18
251
1
Order By: Relevance
“…(1) Helfer et al (2003); (2) Sofue et al (1999); (3) Lu et al (1993); (4) Zimmer et al (2004); (5) Kamphuis & Briggs (1992); (6) Moustakas et al (2010); (7) Cedrés et al (2004). Foyle et al (2010), using a multiband analysis from H I to the far-UV for the grand design galaxies NGC 5194, NGC 682, and NGC 6946, found that there is no shock trigger, and that the spiral arms just reorganize the material from the disc, which will generate stars as a function of gas density, following a KennicuttSchmidt law, for example (Kennicutt 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…(1) Helfer et al (2003); (2) Sofue et al (1999); (3) Lu et al (1993); (4) Zimmer et al (2004); (5) Kamphuis & Briggs (1992); (6) Moustakas et al (2010); (7) Cedrés et al (2004). Foyle et al (2010), using a multiband analysis from H I to the far-UV for the grand design galaxies NGC 5194, NGC 682, and NGC 6946, found that there is no shock trigger, and that the spiral arms just reorganize the material from the disc, which will generate stars as a function of gas density, following a KennicuttSchmidt law, for example (Kennicutt 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the velocity of stars does not decrease at high radius, but rather asymptotes to a constant, indicating an interior mass function M (r) ∝ r. As the luminous interior mass grows much more slowly than this, these curves imply contributions from a significant dark matter component [21]. [21].…”
Section: Galactic Rotation Curvesmentioning
confidence: 98%
“…Note that the velocity of stars does not decrease at high radius, but rather asymptotes to a constant, indicating an interior mass function M (r) ∝ r. As the luminous interior mass grows much more slowly than this, these curves imply contributions from a significant dark matter component [21]. [21]. A collection of galactic rotation curves from [21] can be seen in Figure 1-6, and Figure 1 -7 [22] shows the contributions of the luminous disk and the dark halo for NGC 3198 specifically.…”
Section: Galactic Rotation Curvesmentioning
confidence: 98%
See 2 more Smart Citations